Second IMO greenhouse gas study 2009 (IMO LondonGB, 2009)
Assesses present and future emissions from international shipping viz, the possibilities for reduction of these emissions through technology and policy; and impacts on climate these emissions.
Keywords: CARBON DIOXIDE